Thinking machines : the quest for artificial intelligence--and where it's taking us next - Dormehl, Luke (New York : TarcherPerigee, 2017)
"A fascinating look at Artificial Intelligence, from its humble Cold War beginnings to the dazzling future that is just around the corner. When most of us think about Artificial Intelligence, our minds go straight to cyborgs, robots, and sci-fi thrillers where machines take over the world. But the truth is that Artificial Intelligence is already among us. It exists in our smartphones, fitness trackers, and refrigerators that tell us when the milk will expire. In some ways, the future people dreamed of at the World's Fair in the 1960s is already here. We're teaching our machines how to think like humans, and they're learning at an incredible rate. In Thinking Machines, technology journalist Luke Dormehl takes you through the history of AI and how it makes up the foundations of the machines that think for us today. Furthermore, Dormehl speculates on the incredible--and possibly terrifying--future that's much closer than many would imagine. This remarkable book will invite you to marvel at what now seems commonplace and to dream about a future in which the scope of humanity may need to widen to include intelligent machines"--
Includes bibliographical references (pages 249-263) and index.
Keywords: Artificial intelligence; Artificial intelligence -- Social aspects; COMPUTERS / Intelligence (AI) & Semantics; SCIENCE / Philosophy & Social Aspects; TECHNOLOGY & ENGINEERING / History